Read till it shatters : nationalism and identity in modern Thai literature - Thak Chaloemtiarana (Asian studies series monograph, 2018)
"This book introduces readers to modern Thai literature through the themes of modernity, nationalism, identity and gender. In the cultural, political and social transformations that occurred in Thailand during the first half of the twentieth century, Thai literature was one of the vehicles that moved the changes. Taking seriously 'read till it shatters', a Thai phrase that instructs readers to take apart the text, to break it down, to deconstruct it, Thak Chaloemtiarana challenges the Thai literary canon from the margins and suggests ways of expanding and enriching it. Thai literature is scarce in translation and requires the skills of a scholar fluent in Thai to comprehend it. Thak is a political scientist turned literary scholar who is bilingual in Thai and English and an avid reader of Thai fiction by authors up and down the social scale. Here he offers lively insights into his favourite literary genres with fresh readings of early Thai novels, Sino-Thai biographies and memoirs of the rich and famous.